INITIATIVE OF CANING PUNISHMENT FOR PERPETRATORS OF WILDLIFE KILLING IN ACEH PROVINCE, INDONESIA - Muhammad Yusuf; Muhammad Habibi MZ; Dedy Sumardi (Kanun Jurnal Ilmu Hukum, 2023)
The initiative to include 'uqubat ta'zir whips as a punishment for those who commit animal killing, as stated in Qanun Aceh Number 11 of 2019 concerning Wildlife Management, has been rejected due to its reference to Law Number 5 of 1990 concerning Natural Resources Conservation. This initiative holds significance in terms of the conceptual understanding and application of caning as a criminal sanction in Indonesia. Through doctrinal methods, this study has determined that caning for perpetrators of animal killing falls under 'uqubat ta'zir, where the form, type, and severity of punishment are determined by the ruler based on philosophical, juridical, and sociological considerations. The implementation of caning for those who commit animal killing is deemed appropriate, as the regulations in Indonesia are founded upon values deeply rooted in the community. Therefore, it is fitting to carry out this punishment, similar to other offenses regulated in the Aceh Qanun Jinayat.